Hereditary multiple osteochondromas in a child: a case report and discussion of postoperative complication management - Jia, Haiting; Wang, Yuting; Liu, Tao (Frontiers in Surgery, 2025)
BackgroundThe pathogenesis of hereditary multiple exostoses is mainly related to genetic variants and often requires surgical resection when it causes clinical symptoms. This case report describes a variant in the EXT1 gene and the management of postoperative femoral artery rupture.Case presentationWe present the case of an 11-year-old boy who developed hereditary multiple exostoses. The patient presented with multiple bone swellings throughout his body and difficulty squatting due to a swelling in his right thigh. Genetic testing showed that the child had a heterozygous variant in the EXT1 gene c.1722+1G>A (p.?). We performed a resection of the osteochondroma of the right femur; however, after the surgery, there was persistent bleeding from the wound. Surgical exploration revealed a rupture of the right femoral artery, which we repaired.ConclusionsThe diagnosis of hereditary multiple exostoses relies on a clinical examination and genetic testing. Surgical resection is indicated for symptomatic cases with functional impairments. To prevent vascular injuries such as femoral artery rupture, meticulous surgical technique is essential, including thorough smoothing of the resected bone surface and a careful intraoperative assessment of the adjacent neurovascular structures. In cases of postoperative bleeding or suspected pseudoaneurysm, prompt imaging and surgical exploration are critical for timely vascular repair.